PENGARUH LOKASI (PLACE), HARGA (PRICE), PELAKU WISATA (PEOPLE) TERHADAP MINAT BERKUNJUNG KEMBALI KE OBJEK WISATA PANTAIPASIR PUTIH PARBABA SAMOSIR - Simarmata, Elisa Friska; Wardani, Nurul (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2018)
This study aims to determine the influence of the place, price, people on the interest of visiting again at the tourist attraction of Pasir Putih Beach Parbaba Samosir. The population in this study as many as 17,182 tourists and using random sampling in sampling technique as much as 100 in the attractions of White Sands Beach Parbaba Samosir. Data collection technique in this research is done by spreading the questionnaire (questionnaire) which measurement with likert scale and processed statistically using multiple regression analysis and testing of t test hypothesis, f test, and coefficient of determination that previously data have been tested using validity test, test realibility, and the classical assumption test. Data processing using SPSS 22.0 for windows. From the results of validity test obtained rhitung> rtabel for each question item and reliability test questionnaire obtained alpha cronbach each variable that is 0.786 for the variable X1, 0.779 for the variable X2, 0.667 for the variable X3 and 0.455 for variable Y. This value is greater from the significant level of rtabel is 0,306. Data analysis of each variable is obtained by multiple regression equation Y = 1,301 + 0,042X1 + 0,049X2 + 0,136X3 + e. Obtained R2 equal to 0,193, which means X1, X2 and X3 explain influence to variable Y equal to 19,3% while the rest explained variable outside tourist object. Partial test produced by each independent variable has an effect on dependent variable with the research significance is smaller than 0.1. The conclusion in this study is the location, price, actors of tourism positih influence on the interest of visiting again at the Object of White Sands Beach ParbabaSamosir Keywords: Place, Price, People, Visitor Interest